Problems of adoption privacy ensuring in considering of civil case on adoption (adrogation) of a child in the courts of the Republic of Kazakhstan - Aliyeva, L.R.; Otarbayeva, A.T. (Bulletin of the Karaganda University “Law Series”, 2022)
This article discusses the main provisions on the adoption privacy in the consideration of a civil case on the adoption of a child in the courts of the Republic of Kazakhstan and the problems of its ensuring. The adoption (adrogation) privacy is considered as the most important category regarding the rights and legitimate interests of the child as independent participator involved in the process of adoption. The protection of the rights of children is one of the priorities of any civilized state. The controversial moments are relevant in the sphere of regulating the adoption privacy, including a procedural nature that is directly related to the protection of the rights and interests of the participants of this process. The authors of the paper aim to determine alternatives to application of provisions on the adoption privacy in civil proceedings based on the analysis of the peculiar-ities of Kazakhstan and foreign regulation of the relations under consideration, considering the norms of an international legal nature. The methodological basis of this work is dialectical, systemic, comparative-legal, regulatory, and other methods of knowledge. Analysis of the current legislation of the Republic of Kazakh-stan allows us to conclude that there is a sufficient number of branch values in it, which ensure the adoption (adrogation) privacy. Despite this, some rules in this area require a certain adjustment and improvement, which will further contribute to more effective legal regulation of these legal relations.